Catabolic Division of Labor Enhances Production of D-Lactate and Succinate From Glucose-Xylose Mixtures in Engineered Escherichia coli Co-culture Systems - Flores, Andrew D.; Choi, Hyun G.; Martinez, Rodrigo; Onyeabor, Moses; Ayla, E. Zeynep; Godar, Amanda; Machas, Michael; Nielsen, David R.; Wang, Xuan (Frontiers in Bioengineering and Biotechnology, 2020)
Although biological upgrading of lignocellulosic sugars represents a promising and sustainable route to bioplastics, diverse and variable feedstock compositions (e.g. glucose from the cellulose fraction and xylose from the hemicellulose fraction) present several complex challenges. Specifically, sugar mixtures are often incompletely metabolized due to carbon catabolite repression while composition variability further complicates the optimization of co-utilization rates. Benefiting from several unique features including division labor, increased metabolic diversity, and modularity, synthetic microbial communities represent a promising platform with the potential to address persistent bioconversion challenges. In this work, two unique and catabolically-orthogonal E. coli ¬cocultures systems were developed and used to enhance the production of D-lactate and succinate (two bioplastic monomers) from glucose-xylose mixtures (100 g L-1 total sugars, 2:1 by mass). In both cases, glucose specialist strains were engineered by deleting xylR (encoding the xylose-specific transcriptional activator, XylR) to disable xylose catabolism, whereas xylose specialist strains were engineered by deleting several key components involved with glucose transport and phosphorylation systems (i.e., ptsI, ptsG, galP, glk) while also increasing xylose utilization by introducing specific xylR mutations. Optimization of initial population ratios between complementary sugar specialists proved a key design variable for each pair of strains. In both cases, ~91% utilization of total sugars was achieved in mineral salt media by simple batch fermentation. High product titer (88 g L-1 D-lactate, 84 g L-1 succinate), maximum productivity (2.5 g L-1 h-1 D-lactate, 1.3 g L-1 h-1 succinate) and product yield (0.97 g g-total sugar-1 for D-lactate, 0.95 g g-total sugar-1 for succinate) were also achieved.